Pathways to power in fragile settings: Rethinking women’s roles in agriculture and food systems - Quisumbing, Agnes R.; Kyle, Jordan; Kosec, Katrina; Ragasa, Catherine (International Food Policy Research Institute, 2025)
Research shows that women play pivotal roles in farming—across value chains, and in food systems as a whole. With harmful effects of climate change, conflict, forced migration, and other problems on the rise, many women around the world find themselves in increasingly fragile settings—creating new challenges in efforts to achieve gender equity and empowerment in food systems.